Improved metastasis‐free survival in nonadjuvantly treated postmenopausal breast cancer patients with chemokine receptor 5 del32 frameshift mutations. Issue 1 (20th May 2014) - Span, P.N.; Pollakis, G.; Paxton, W.A.; Sweep, F.C.G.J.; Foekens, J.A.; Martens, J.W.M.; Sieuwerts, A.M.; van Laarhoven, H.W.M.
<x xml:space="preserve">Abstract</x> The CC‐chemokine receptor CCR5 has been associated with cancer progression and metastasis. CCR5 blockers such as Maraviroc are tested in metastatic cancer patients. A mutant allele of CCR5, CCR5‐delta32 (CCR5del32), which encodes for a protein with a trans‐dominant negative effect on the wildtype protein, is frequently found in populations of northern European origin. We set out to determine if the CCR5del32 genotype is associated with progression of breast cancer. Here, we genotyped 414 breast cancer patients and investigated whether the CCR5 genotype had an association with the likelihood to metastasize within specific subgroups of this cohort. The findings were subsequently confirmed in an independent cohort of 1, 017 breast cancer patients. Specifically within the postmenopausal subgroup of the initial cohort (n = 325) individuals carrying the CCR5del32 genotype exhibited a significantly longer metastasis‐free survival (MFS, p = 0.038). In an independent cohort, CCR5del32 genotype was confirmed to be associated with prolonged MFS only in postmenopausal patients (n = 579, hazard ratio [HR] = 0.61, 95% confidence interval [95% CI] = 0.38‐0.99, p = 0.044), and not in premenopausal patients (n = 438, HR = 1.01, 95% CI = 0.70–1.48, p = 0.94). Our results indicate that CCR5del32 genotype is associated with good prognosis in postmenopausal breast cancer patients. Considering this result, postmenopausal breast cancer patients who are wildtype for CCR5 genotype might benefit from CCR5 blockers, such as Maraviroc.